Evaluating the Educational Impact of Studio-Based Design Methodologies in Architectural Courses - Khan, Hasibullah; Niazi, Ahmad J. (International Journal of Architectural Engineering Technology, 2025)
Architecture studios are essential in teaching design skills. Exploring how different design methodologies impact student performance helps improve education, fostering creativity, critical thinking, and better learning outcomes in architecture programs. The objective of the research is to examine the impact of various design methodologies on student achievement in architecture studios, identifying effective teaching approaches that enhance creativity, critical thinking, and overall performance in architectural education. The research involved 526 architecture students as participants. Data were collected using structured surveys to identify design methodologies and academic performance records. The software IBM SPSS Statistics version 17.0 was used to perform these statistical analyses including correlation coefficients, multiple linear regressions (MLR), ANOVA and paired t-test to examine the relationship between teaching methodologies and student achievement, providing insights into their impact on performance. Examined five factors: collaborative learning, iterative processes, instructor feedback, problem-solving skills, and time management. These factors were analyzed to determine their influence on student creativity, critical thinking, and overall achievement in architecture studio projects. The outcomes revealed a significant positive correlation among specific design methodologies and student achievement. Collaborative and iterative approaches showed the strongest impact on creativity and performance. Collaborative and iterative methodologies significantly enhance student achievement, highlighting the importance of effective teaching strategies in architecture studios.